1996
DOI: 10.1108/02651339610131379
|View full text |Cite
|
Sign up to set email alerts
|

Methodological issues in cross‐cultural marketing research

Abstract: Notes that methodological problems are hampering the growth of cross‐cultural marketing research and presents a review of methodological issues to address these problems. Organizes these issues around a six‐step framework which includes elements such as problem definition, the development of an approach and research design formulation. Notes that the marketing research problem can be defined by comparing the phenomenon or behaviour in separate cultural contexts and eliminating the influence of the self‐referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
320
0
13

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(333 citation statements)
references
References 90 publications
0
320
0
13
Order By: Relevance
“…In addition, the Anglo-Saxon countries are amongst the most economically developed in the world (e.g., The Economist, 2005; United Nations, 2005a), and amongst the countries that utilize the most sophisticated customer service techniques globally (see, for example, Tellis, Stremersch.& Yin, 2003;Malhotra, Agarwal & Peterson, 1996). There has been some recent confirmatory empirical work outside the Anglo-Saxon cultural cluster (Tschan et al, 2005), whose focus, however, bore limited relevance to the focus of the present study.…”
Section: Emotion Work and Work Attitudes In Hellas 10mentioning
confidence: 80%
“…In addition, the Anglo-Saxon countries are amongst the most economically developed in the world (e.g., The Economist, 2005; United Nations, 2005a), and amongst the countries that utilize the most sophisticated customer service techniques globally (see, for example, Tellis, Stremersch.& Yin, 2003;Malhotra, Agarwal & Peterson, 1996). There has been some recent confirmatory empirical work outside the Anglo-Saxon cultural cluster (Tschan et al, 2005), whose focus, however, bore limited relevance to the focus of the present study.…”
Section: Emotion Work and Work Attitudes In Hellas 10mentioning
confidence: 80%
“…Culture as a new dimension was added (Paul and Alain,1996;Malhotra, Agarwal, & Peterson, 1996;Malhotra et al,1994;Malhotra et al, 2005;Mattila, 1999;Winsted, 1997;Liu and McClure, 2001;Karen and Boo, 2007;Satyabhusan et al, 2009) have identified culture to be an important aspect in measuring service quality context. Public transportation is no exception, (Pe´rez et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Cross-cultural research has increased in importance within an international context [57] and is complemented by the qualitative nature of this study. In order to gain rich data sets and understand consumers' perceptions of the environmental information displayed on FMCGs focus groups were chosen as a research method [58].…”
Section: Methodsmentioning
confidence: 99%